Motion: A Work for Orchestra. - Donmezer, Cagdas. (2017)
Abstract: Motion is an orchestral piece, which consists of three main ideas and their development. The piece was composed for the Tufts Symphony Orchestra. The premiere took place in April 21st 2015, at Distler Performance Hall - Tufts University in Medford, MA- with Tufts Symphony Orchestra under the direction of John Page. The piece is dedicated to my well-beloved mentor and supporter who enlightens my path. To Dr. Kayihan ARIC with deepest respect and affection.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Music.; Advisor: John McDonald.; Committee: Frank Lehman, and Arnold Friedman.; Keyword: Music.